Development of a Four-Tier Multiple-Choice Test on The Concept of Transport Across Membranes - Brian Ricard Wola; Muslimin Ibrahim; Tarzan Purnomo (Universitas Muhammadiyah Sidoarjo, 2020)
The development and use of diagnostic tests in the form of multiple choice four levels in biology learning are still lacking. This study aims to develop a valid and reliable four-tier multiple-choice test instrument to identify the conception profile of high school students on the concept of transport across membranes. The research method is in the form of development research by adapting the Kilic and Saglam models which consist of three stages, namely defining content, obtaining information on student misunderstandings, and developing tests. The research instruments used were validation sheets, test instruments, and interview sheets. Descriptive statistical analysis techniques were used to analyze the data in this study. The results showed that 15 items developed were declared valid and the reliability coefficient of the test was 0.82, including the very reliable category. Thus, it can be concluded that the four-tier multiple-choice test instrument developed has met the validity and reliability requirements to identify the conception profile of high school students about the concept of transport across membranes. The four-tier multiple-choice test developed can be used by high school teachers as an accurate test to identify the conception profile of their students because it can distinguish between students who understand the concept, do not understand the concept, or who experience misconceptions about the concept of transport across membranes.